Fundamentos para concepção, controle e automação de uma planta armazenadora de energia utilizando hidrogênio - Gonzatti, Frank (2017)
Electrical generation with renewable sources is intermittent due to the characteristics of the primary energy (sun, wind, run of water, etc.). This feature can cause fluctuations and distortions on the voltage levels compromising power quality, stability and reliability when connected to an electrical system. The storage of energy acting together either as standalone unit or interconnected to the generating source of the public network can increase the penetration of these sources in the energy matrix. Among the different forms of energy storage, the one using hydrogen is quite promising because of its characteristics such as low environmental impact, high energy density, and energy high storage capacity. In this thesis, it is proposed some basis for designing, controlling and analyzing a hydrogen-based energy storage plant, consisting of a set of an alkaline type electrolyzer, hydrogen storage in the form of metallic hydrides and a fuel cell stack of the type PEM. The proposed plant was modeled and validated through experimental tests. The model allowed simulation of the main physicochemical quantities involved in the process of generation, storage and conversion of hydrogen into electricity storage. The fuel cell stack that is part of the energy storage was automated to avoid damages to the membrane, acting mainly on temperature control, elimination of contaminants on the anode side, and voltage reestablishment through the controlled application of short-circuits. The metal hydride cylinder storing hydrogen has been also automated with the main purpose of performing a thermal exchange in the best possible way between the metal alloy and the environment. Reuniting these devices to make them to act in synchrony, the plant was automated, controlled and monitored through a software developed in the LabView platform, making it more autonomous the whole plant. This program allows also acquisition and storage of the main physico-chemical quantities during the plant operation. These magnitudes collected in the tests along with the simulation results were analyzed and characterized the fundaments of this thesis.